Long‐Term Effect of Deslorelin Implant on Ovarian Pre‐Antral Follicles and Uterine Histology in Female Rats. Issue 2 (9th June 2012) - Cetin, Y; Alkis, I; Sendag, S; Ragbetli, M; Akyol, V; Ucar, O; Wehrend, A
Contents The objective of the present study was to investigate the inhibitory effects of long‐term deslorelin implant administration on the ovarian and uterine structures of female rats. A total of 16 non‐pregnant female rats were randomly assigned to two groups, each consisting of eight animals. Animals in the implant group (DESL) received subcutaneously (s.c.) a single deslorelin implant (4.7 mg), an analogue of GnRH, while no treatment was applied to the control group (CON). A single adult male rat was introduced into the cages of both the DESL and CON females after 6 weeks of implant administration. After 1 year of implant administration, all animals were killed and follicular structures and volumes of ovaries and uterus were examined using stereological methods. Stereological observations showed that the mean ovarian total volume of the DESL group (0.28 ± 0.07 cm3) was lower than that of the CON group (1.55 ± 0.23 cm3) (p < 0.001). On the other hand, the total number of pre‐antral follicles in the ovaries of DESL (555.32 ± 151.47) females were significantly lower than the control group (1162.96 ± 189.19) (p < 0.001). In the DESL group, the mean volumes of epithelium, endometrium, myometrium and total volume of the uterus were significantly (p < 0.001) lower than in the control groups. In conclusion, these findings indicate that the long‐term deslorelin implant (i) interferes with the normal cyclicity of female rats and (ii) affects the pre‐antral follicle population. Further studies will be required to determine the effects of long‐term deslorelin treatment on the pre‐antral follicle numbers and future fertility in other species.